Dynamic interplay of metal and metal oxide nanoparticles with plants: Influencing factors, action mechanisms, and assessment of stimulatory and inhibitory effects - Rabia Javed; Bakhtawar Khan; Uzma Sharafat; Muhammad Bilal; Lakshman Galagedara; Lord Abbey; Mumtaz Cheema (Ecotoxicology and Environmental Safety, 2024)
Nanoparticles (NPs) of metals and metal oxides have received increasing attention regarding their characteristic behavior in plant systems. The fate and transport of metal NPs and metal oxide NPs in plants is of emerging concern for researchers because they ultimately become part of the food chain. The widespread use of metal-based NPs (MBNPs) in plants has revealed their beneficial and harmful effects. This review addresses the main factors affecting the uptake, translocation, absorption, bioavailability, toxicity, and accumulation of MBNPs in different plant species. It appraises the mechanism of nanoparticle-plant interaction in detail and provides understanding of the estimation strategies for the associated pros and cons with this interplay. Critical parameters of NPs include, but are not limited to, particle size and shape, surface chemistry, surface charge, concentration, solubility, and exposure route. On exposure to MBNPs, the molecular, physiological, and biochemical reactions of plants have been assessed. We have filled knowledge gaps and answered research questions regarding the positive and negative effects of metal and metal oxide NPs on seed germination, callus induction, growth and yield of plant, nutritional content, antioxidants, and enzymes. Besides, the phytotoxicity, cytotoxicity, genotoxicity, and detoxification studies of MBNPs in plants have been outlined. Furthermore, the recent developments and future perspectives of the two-way traffic of interplay of MBNPs and plants have been provided in this comprehensive review.